1990
DOI: 10.1097/00006842-199001000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Social support reduces cardiovascular reactivity to psychological challenge: a laboratory model.

Abstract: In this study we investigated the effects of nonevaluative social interaction on the cardiovascular response to psychological challenge. Thirty-nine college-age females appeared accompanied ("Friend" condition) or unaccompanied ("Alone" condition) to an experimental laboratory. In the Friend condition, partners were present while the subject participated in two laboratory tasks, and the partners' evaluation potential was minimized by design. Subjects in the Friend condition showed reduced heart rate reactivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
238
3

Year Published

1997
1997
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 373 publications
(264 citation statements)
references
References 37 publications
23
238
3
Order By: Relevance
“…Previous studies have shown that the support of a friend rather than a stranger was, in the main, associated with reduced reactivity (19)(20)(21)(22)(23). What the present data add is that the sex of the supporter is important in determining whether this attenuation effect is observed; support from a male friend was associated with relatively reduced BP reactivity whereas support from a female friend was associated with increased BP reactivity.…”
Section: Discussionsupporting
confidence: 43%
“…Previous studies have shown that the support of a friend rather than a stranger was, in the main, associated with reduced reactivity (19)(20)(21)(22)(23). What the present data add is that the sex of the supporter is important in determining whether this attenuation effect is observed; support from a male friend was associated with relatively reduced BP reactivity whereas support from a female friend was associated with increased BP reactivity.…”
Section: Discussionsupporting
confidence: 43%
“…Reminders of supernatural allies appear to attenuate risk perception, paralleling the role of social support in reducing anxiety in challenging circumstances (Kamarck, Manuck, & Jennings, 1990), and consistent with understandings of supernatural entities as capable of protecting believers from harm. Subtle reminders of God have been observed to increase willingness to take physical risks, an effect mediated by decreased perceptions of the self as likely to be injured (Kupor, Laurin, & Levav, 2015).…”
Section: Introductionsupporting
confidence: 56%
“…The presence of social support may also attenuate blood pressure and heart rate responses to stressful stimuli in humans. 140,141 In summary, these data suggest that social factors promote atherogenesis through activation of the autonomic nervous system.…”
Section: Socioeconomic Statusmentioning
confidence: 76%